1976
DOI: 10.1007/bf01405865
|View full text |Cite
|
Sign up to set email alerts
|

The blink reflex in coma and after recovery from coma

Abstract: Comparative studies of the blink reflex in a series of head injuries through the stages of coma and recovery from coma in a series of miscellaneous hemispheral lesions, and in a normal series, reveals that, although the principal centre for the R1 component of the blink reflex seems to be localised in the upper pons, the seat of the R2 late component is in the reticular system. The reappearance of this late component of the blink reflex in our cases of coma although seeming to depend on the integrity of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
3
4
0
1
Order By: Relevance
“…The correlation of coma grade and BR changes demonstrated that prognosis is better when R2 is present [14]. A close correlation has been reported between survival and a positive R1 during the first investigation [27], followup recordings having a high predictive value [27,104,113].…”
Section: Blink Reflexsupporting
confidence: 41%
“…The correlation of coma grade and BR changes demonstrated that prognosis is better when R2 is present [14]. A close correlation has been reported between survival and a positive R1 during the first investigation [27], followup recordings having a high predictive value [27,104,113].…”
Section: Blink Reflexsupporting
confidence: 41%
“…The effects of altered consciousness on the blink reflex have been studied in and coThe effects of ether13 and barbituma*15, [47][48][49] rate13'16 anesthesia have been studied in animals. In a recent study of intraoperative recording of blink reflexes in patients with hemifacial spasm under isoflurane and nitrous oxide anesthesia, it was reported that "the blink reflex cannot normally be elicited during surgical anesthesia using inhalation anesthetic^.…”
Section: Head 81 Neck 11937-1491989supporting
confidence: 38%
“…In the human medical world, absence of the corneal reflex is considered a worrying sign of brainstem damage (Cruccu et al, 1997). When the corneal reflex cannot be evoked, there is a large probability that the disruption is associated with a wider dysfunction, comprising part of the reticular formation, and thus with a state of unconsciousness (Serrats et al, 1976;Cruccu et al, 1997;Laureys, 2005;Terlouw et al, 2016b). In the study described in Chapter 5, none of the pigs subjected to 80% or 95% CO 2 had a corneal reflex following stunning.…”
Section: Eye Reflexessupporting
confidence: 42%